2020
DOI: 10.1007/s42976-020-00067-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of QTL for phosphorus efficiency and biomass traits at the seedling stage in wheat

Abstract: Phosphorus (P) is one of the most vital nutrient elements in crop output and quality formation. In this study, four biomass, four P uptake efficiency (PupE), and three P-utilization efficiency (PutE) traits were investigated using a set of recombinant inbred lines (RILs) derived from a cross of "SN0431 × LM21", under hydroponic culture trials at low P (LP) and normal P (NP) levels in two different seasons, respectively. A total of 85 QTL were identified on 18 chromosomes except for 1D, 2A, and 3D. Among them, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Similarly, previous research has been reported ( Su et al., 2009 ; Vijayalakshmi et al., 2010 ; Yang et al., 2016b ). The majority of chlorophyll content QTLs detected under CK, MP, and LP conditions are different, indicating that the chlorophyll regulation mechanism under low phosphorus conditions may differ from that under normal phosphorus conditions, and similar phenomena have been observed in previous research ( Yang et al., 2018 ; Yuan et al., 2020 ; Yang et al., 2021 ). Under multiple phosphorus conditions, six major QTLs Qchl.saw-2B.1 , Qchl.saw-3B.1 , Qchl.saw-4D.1 , Qchl.saw-4D.2 , Qchl.saw-5A.9 and Qchl.saw-6A.4 were detected ( Table 4 ).…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, previous research has been reported ( Su et al., 2009 ; Vijayalakshmi et al., 2010 ; Yang et al., 2016b ). The majority of chlorophyll content QTLs detected under CK, MP, and LP conditions are different, indicating that the chlorophyll regulation mechanism under low phosphorus conditions may differ from that under normal phosphorus conditions, and similar phenomena have been observed in previous research ( Yang et al., 2018 ; Yuan et al., 2020 ; Yang et al., 2021 ). Under multiple phosphorus conditions, six major QTLs Qchl.saw-2B.1 , Qchl.saw-3B.1 , Qchl.saw-4D.1 , Qchl.saw-4D.2 , Qchl.saw-5A.9 and Qchl.saw-6A.4 were detected ( Table 4 ).…”
Section: Discussionsupporting
confidence: 79%
“…In another study, a single quantitative trait locus associated with RDW in 142 RILs derived from two Chinese winter wheat varieties (Xiaoyan 54 × Jing 411) was identified [35]. A total of 176 RILs of wheat derived from Shannong 0431 × Lumai 21 were used to detect more than two QTL for SDW and RDW under LP conditions, using 5916 SSR markers [28]. Seven QTL associated with RDW were determined in 241 RILs of maize derived from the cross of 082 and Ye107 genotypes under LP conditions [91].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 QTL associated with plant height (PH), shoot length (SL), number of productive tillers (NPT), panicle length (PL), shoot dry weight (SDW), seed yield (SY), plant biomass, root-shoot ratio (RSR), and seed P content (SPC) were identified in rice (Oryza sativa) under LP conditions [24]. Similarly, 36 QTL associated with SDW; root dry weight (RDW); total dry weight (TDW); RSR; shoot P content; total P content (TPC); and shoot, root, and total P-utilization efficiency were identified in wheat (Triticum aestivum) under LP conditions [28]. Gao et al, 2020 identified several QTL for PAE-, PUE-, and yield-related traits at the maturity stages in 128 recombinant inbred lines (RILs) of barley (Hordeum vulgare) under LP conditions [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the localization of T. aestivum PSTOL1 orthologs with QTLs for morpho-physiological and biochemical traits under phosphorus starvation, QTLs and linked molecular markers were retrieved from previous publications [ 38 , 39 , 40 , 41 , 42 , 43 ], and co-localization was shown as described previously in [ 44 ]. To obtain the physical position, each marker sequence or marker name was BLAST against the grain gene database [ 45 ].…”
Section: Methodsmentioning
confidence: 99%